Hypofractionated External-Beam Radiotherapy for Prostate Cancer - L. Chinsoo Cho; Robert Timmerman; Brian Kavanagh (Prostate Cancer)
There are radiobiological rationales supporting hypofractionated radiotherapy for prostate cancer. The recent advancements in treatment planning and delivery allow sophisticated radiation treatments to take advantage of the differences in radiobiology of prostate cancer and the surrounding normal tissues. The preliminary results from clinical studies indicate that abbreviated fractionation programs can result in successful treatment of localized prostate cancer without escalation of late toxicity.